Neurodivergent patient experience in a tertiary children's hospital-a qualitative analysis - Talley, Michele; Brown, Chelsea; Wingo, Nancy; Conway, Jennifer; Maha, Julian; Kong, Michele (Frontiers in Pediatrics, 2024)
Introduction: Sensory processing challenges are commonly encountered in pediatric patients, particularly in those who are neurodivergent. We previously developed a novel clinical pathway (named 'Sensory Pathway') which aimed at improving patient care for those with sensory barriers via staff training, provision of sensory toolkits and early integration of families throughout the hospital stay. We hypothesized that utilization of this pathway will result in improved patient experience and provide valuable feedback to improve care.A voluntary survey was made available to all patients who utilized this resource as part of our hospital wide patient satisfaction survey. Qualitative data was coded using open coding as part of the constant comparison method data using NVivo 12 for Windows software for analysis. Software was used to create word clouds and clusters for visualization, which confirmed the themes and patterns that were noted from initial open coding.Results: Between 2021-2022, surveys were obtained from 160 patients who utilized the Sensory Pathway. More than 50% reported that the most helpful components of the pathway were the approach by the staff and sensory tools. The three major themes identified from the survey were 1. Tools and techniques that benefited their children; 2. Positive interactions and communication with the hospital staff, and 3. Suggestions for future improvement.The survey results highlight the importance of having tools readily available to aid with sensory regulation and comfort of patients during healthcare encounters, the value of a positive patient and staff encounter, as well as opportunities for improvement.